An integrated supplier selection approach in supply chain system under fuzzy environment - Bhayana, Nidhi; Gandhi, Kanika; Aditi; Jha, Prakash C. (Yugoslav Journal of Operations Research, 2019)
Due to the increasing awareness and government policies towards environmental sustainability, organizations are extending their efforts to enhance environmental practices in their Supply Chain (SC). At the same time, they are integrating their SC activities in such a way so as to reduce system cost while satisfying the needs of their consumers. Thus, organizations collaborate with the efficient suppliers in order tomeet the quality level and customers requirements in terms of economic and environmental aspect. In this study, an optimization mathematical model is formulated for selecting suppliers with respect to interrelated criteria while taking care of ecological feature. An application is illustrated on an Indian manufacturing company of microwave oven. We propose an integrated supplier selection approach that consists of three stages. In the first stage, a dimension reduction method is utilized to group the variables as per interrelated criteria. An integrated methodology of mean and standard deviation along with Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) is employed in the second stage for assessing the performance of suppliers in quantitative terms. The final stage comprises of a bi-objective mathematical model. The model is formulated to minimize the system cost while simultaneously minimizing carbon emission. The model helps in efficient identification of the procurement amount of products and the appropriate distribution center (DC), which is based on customers demand and the DC capacity to deliver goods to the Retail Stores (RSs). A fuzzy goal programming approach is utilized further to create a trade-off between two contradictory goals of the optimization model. The results suggest that integrating environmental with economical aspect can improve the performance of the SC network.